ATA ENCRYPTION USING THE CHAOTIC DYNAMICS IN WIRELESS SENSOR NETWORKS - A. V. Sidorenko; K. S. Mulyarchik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The block-diagram for transmission of the encrypted information in wireless sensor networks is presented. For the encryption algorithm based on the symmetric algorithmic diagram the chaotic systems and maps are used. The dynamic chaos based encryption algorithm features the advantages (higher level of defense of the information about the routing; better reliability and data carrying capacity) which extend the scope of the cryptographic problems solved. The hardware and the software are realized with an ultra wideband transmitter- receiver of the PPS-40A type. Installation of the software in microcontroller of the PPS-40A type transmitter-receiver is illustrated. The characteristics of the transmitter-receiver microcontroller code before and after the encryption function realization are given. The peculiarities in implementation of the hard- and software for the encryption algorithm are considered.